PERBANDINGAN TINGKAT KEPUASAN ATLET ANTARA PENGGUNAAN ALAT DIGITAL SCORING SYSTEM (DSS) DENGAN PROTECTOR SCORING SYSTEM (PSS) PADA PERTANDINGAN CABANG OLAHRAGA TAEKWONDO NOMER KYORUGI - Pratama, Aldipa Rizkia (2014)
Hampirsemuacabangolahraga diduniasaatinisedangberevolusimemanfaatkankemajuanilmupengetahuandanteknologiuntukmendorong agar kegiatanolahraga, terutamadalampertandinganmemperolehhasilpenilaian yang lebihobyektif. Salah satunyaadalahpenggunaanalatdigital scoring system (DSS)danProtector Scoring System (PSS), namunkeduaalattersebutmasihbanyakmengalamigangguansaatpertandingan, sehinggadapatmempengaruhikeobjektifanpenilaianwasit.Tujuanpenelitianiniadalahuntukmenelaahperbandingankepuasanatletdalampenggunaanalat digital scoring system (DSS) danprotector scoring system (PSS) padaatlet taekwondo kota Bandung. Sampeldiambilsebanyak 30 orang atlet taekwondo kota Bandung menggunakanteknikpurposive sampling.Metodepenelitian yang dipakaiadalahdeskriptifkompartif.Pengumpulan data menggunakan instrument angketkepuasanatlet.Penghitunganstatistikmenggunakan SPSS dengan sub menu independent sample T-test. Dari hasilanalisis data angketkepuasanatletdiperolehbahwaskorkepuasan DSS adalah 923 dengan rata-rata 30,77 danskor PSS adalah 1257 dengan rata-rata 41,9. Diperoleh pula nilai p<0,05. Hasilpenelitianinimenunjukanbahwaterdapatperbandingankepuasan yang signifikanantarapenggunaanalatdigital scoring system (DSS) denganprotector scoring system (PSS).Dimanaatletlebihpuasmenggunakanprotector scoring system (PSS) dibandingkandengandigital scoring system (DSS) Almost all sports in the world today is being evolved utilizing advanced science and technology to encourage sports activities, especially in the game gain a more objective assessment. One is the use of digital tools scoring system (DSS) and Protector Scoring System (PSS), but both of these tools are still much impaired during the game, so that could affect the objectivity of assessment judge. Purpose this study is to examine the ratio of athlete satisfaction in the use of digital tools scoring system (DSS) and protector scoring system (PSS) in Bandung taekwondo athletes. Samples were taken as many as 30 people taekwondo athlete Bandung using purposive sampling technique. The research method used is descriptive compartive. Collecting data using the athlete satisfaction questionnaire instrument.Counting statistics using SPSS with sub menus independent sample T-test. From the analysis of data obtained by the athlete satisfaction questionnaire that DSS satisfaction score was 923 with an average of 30.77 and PSS score was 1257 with an average of 41.9. Obtained the value of p <0.05. These results indicate that there is significant satisfaction comparison between the use of digital tools scoring system (DSS) with protector scoring system (PSS). Where athletes are more satisfied using a protector scoring system (PSS) compared with digital scoring system (DSS)